Management of cataract in keratoconus: early visual outcomes of different treatment modalities - Nicolas Arej; Wassef Chanbour; Karen Zaarour; Mazen Amro; Hala El-Rami; Fadi Harb; Elias Jarade (International Journal of Ophthalmology, 2019)
A review of 31 eyes with keratoconus who developed cataract and underwent phacoemulsification. Visual acuities were measured 1mo postoperatively. Six eyes with a history of good corrected distance visual acuity (CDVA) and a similar refractive and topographic astigmatic axis were implanted with toric intraocular lenses (IOLs). The mean postoperative uncorrected distance visual acuity (UDVA) was 0.2 logMAR with a spherical equivalent (SE): 0.75D. Eleven eyes with a history of good CDVA and different refractive and topographic axis were implanted with monofocal IOL+/-Toric implantable collamer lenses to treat anisometropia and ametropia; mean UDVA was 0.25 logMAR with a mean SE: -0.51 D postoperatively. Six eyes with poor CDVA were first treated with intra-corneal ring segments, followed by phacoemulsification, the mean postoperative UDVA was 0.82 logMAR with an SE: 0.22 D. Eight eyes had advanced ectesia and received combined phacoemulsification and penetrating keratoplasty. Our approach is efficient in addressing ametropia after cataract surgery in keratoconic eyes.